A keleti templom ikonográfiája és a vizuális kommunikáció - Cserbák András (2001)
The study introduces the structure of the liturgical space and the biblical theological background of the Eastern Church and compares it with the analysis of the dramatic customs. The Eastern Church is the analogy of the cosmos. Its pictures illustrate the posthumus/post motrem part of God's people and those who take part in the liturgy are the prehumous ones. Together they from the sacred theatre, the one and indivisible reality. The author thinks that the results of the analysis in Eastern liturgical space and ceremony are applicable for the research in rituals/rites and customs in general.
Keywords: Bölcsészettudományok; Történettudomány és régészet; Filozófia, etika és vallástudományok